Propagation model for 2.4 GHz wireless sensor network in four-year-old young apple orchard - Xiuming, Guo; Chunjiang, Zhao (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Wireless sensor network (WSN) nodes exchange information via wireless signals, whose power can attenuate at different levels according to the propagation environment. The branches and leaves of young apple trees are much sparser than that of adult apple trees. Propagation rules such as propagation distance and attenuation rate are the parameters necessary to know before applying a WSN to a young apple orchard. Field tests were performed, and propagation distance and packet loss rate (PLR) were computed and compared under the two cases: a young apple orchard in fruit period and an open space to find the effect of the apple trees on radio propagation. A model of antenna height and propagation distance was created to forecast the extra path loss caused by the young trees. Validation experiments were performed in a different young apple orchard, and the validation results showed that 70% of R2 were higher than 0.7, while the smallest being 0.65; 80% RMSE were smaller than 5. The new model was also compared with some classical models such as Cost 235, FITU, ITU-R, and Weissberger model, and the new model was proved to be the best.Keywords: wireless sensor network (WSN), propagation model, packet loss rate, 2.4 GHz, young apple orchardDOI: 10.3965/j.ijabe.20140706.007Citation: Guo X M, Zhao C J. Propagation model for 2.4 GHz wireless sensor network in four-year-old young apple orchard. Int J Agric & Biol Eng, 2014; 7(6): 47－53.